Out-of-Plane Flexural Behavior of Reinforced Masonry Walls Strengthened With Near-Surface-Mounted Fiber-Reinforced Polymer - Al-Jaberi, Zuhair; Myers, John J.; ElGawady, Mohamed A. (ACI structural journal, 2018)
Eighteen reinforced masonry walls were built as a part of this study. These reinforced walls were strengthened with carbon fiberreinforced polymer (FRP) bars and strips and glass FRP bars using a near-surface-mounted (NSM) technique; different mild steel reinforcement ratios (ρ) were used. These simply supported walls were tested under an out-of-plane cyclic load that was applied along two line loads. Various parameters were investigated, including those related to FRP (type and amount), bond pattern (stack and running), mortar pattern (face shell bedding and fully bedding), embedding material (epoxy and cementitious paste), amount of internal steel reinforcement, existence of compression FRP bars, and groove size. The ultimate load, deflection at ultimate load, and mode of failure were investigated in this study. The test results indicated a significant increase in stiffness and flexural capacity of out-of-plane reinforced walls strengthened with FRP compared to the unstrengthened reinforced walls. Different modes of failure occurred in the strengthened reinforced walls, including flexure- shear failure through the concrete block, as well as debonding of FRP reinforcement from the masonry substrate. Furthermore, a simple analytical model for computing the moment capacity of strengthened reinforced masonry walls is proposed and compared with the experimental results.